Investigation and analysis of fracture failure of TS-110 coiled tubing used in oil and gas field in southwest China. (May 2023) - Qu, Ting-ting; Tong, Ke; Li, Hong; Zhao, Jin-lan; Shen, Dan; Song, Juan
Highlights: At present, researches mainly focus on fatigue, buckling and corrosion failure modes and prevention of coiled tubing. The material problem of coiled tubing body leading to its failure is rarely studied. The effects of martensite in coiled tubing banded structure on coiled tubing service life were studied. Accidents caused by material problems in coiled tubing operations cannot be ignored. This research is of significance to improve coiled tubing manufacturing quality, improve inspection standards and methods. Abstract: TS-110 coiled tubings used in drilling operations rarely fracture and fail after only five cycles. In this study, a failed coiled tubing was analysed by conducting various experiments. The experiments included macroscopic observation, outside diameter and wall thickness measurement, physical and chemical inspection, magnetic particle inspection, Vickers hardness test, optical microscopy, scanning electron microscopy, and energy dispersive spectrometry. The results revealed a band structure composed of granular bainite and martensite at the centre of the wall thickness. In addition, the formation of martensite influenced the uniformity of local tensile properties. During coiled tubing operations, martensite with undesirable plasticity cracked and formed microscopic voids which continued to expand. Finally, when the coiled tubing was lifted to the tubing reel for bending deformation, the tensile stress on the outer arc surface reached its maximum value. Moreover, the cracks in this part first penetrated the wall thickness, which triggered cracking and tubing failure.